Unlocking the global benefits of Earth Observation to address the SDG 6 in situ water quality monitoring gap - Wilson, Harriet; Raasakka, Nina; Spyrakos, Evangelos; Millar, David; Neely, Merrie Beth; Salyani, Anham; Pawar, Shubham; Chernov, Igor; Ague, S. Karen de Lespérance; Aguilar Vega, Ximena; Akinsemolu, Adenike; Baltodano Martinez, Analy; et al. (Frontiers in Remote Sensing, 2025)
Achieving Sustainable Development Goal 6 requires innovative and often disruptive approaches to address critical gaps in global water quality monitoring. The most recent SDG Indicator 6.3.2 (Proportion of bodies of water with good ambient water quality) progress report highlights a critical water quality in situ data gap, with an urgent need for countries to strengthen their monitoring capacity and commence state water quality assessments and trend analysis. Earth Observation (EO) technologies hold immense potential to close that gap for SDG Indicator 6.3.2. However, limited awareness, lack of skills and resource inequalities are some of the barriers which hinder widespread adoption of EO. We present insights from a unique workshop held at the University of Stirling in 2024, which convened diverse participants from academia, industry, NGOs, and international agencies and across disciplines, geographies, and sectors. Through creative and collective thinking approaches, they developed four actionable concepts: (1) Space Buzz: a media campaign to raise awareness of EO value; (2) centralised EO access hubs to empower users and improve equality; (3) scalable education strategies for capacity building; and (4) an Intergovernmental Panel for Water Quality to enhance global coordination. Each concept derived from a synoptic creative process, demonstrating the uniqueness of thinking within the teams. To unlock the potential of EO for global water quality monitoring, we invite EO networks, funders, water resource managers and individuals to champion these concepts, and incorporate them into funding calls and proposals.